Փոխառյալ բառերն անգլերենում - Հասմիկ Աբրահամյան (ՀՀ ԳԱԱ հրատ.)
Каждому языку свойствены заимствованные слова, которые имеют большое влияние на эволюционном развитии устной и письменной речи данного языка. В статье рассматриваются заимствованные слова, проникшие в английский язык из различных языков, и их роль на лексико–грамматическое и фонетическое развитие языка. В статье также представлен список ряда заимствованных слов, имеющих свое стабильное место в лексике современного английского языка, которые, несомненно, представят интерес для студентов и всех интересующихся английским языком. Borrowed words (loan words) are typical for every language and have a great influence on the evolutionary development of spoken and written languages. The given article deals with borrowed words (loan words) penetrated into the English language from a variety of languages and their role in phonetic language development. The article also lists a number of borrowed words having found their stable place in the word stock of modern English. Undoubtedly, the article will be interesting for students and those, who are interested in the English language.
Keywords: Philology; Linguistics; Language and Literature; English